Implementasi Equal Employment Opportunity dan Affirmative Action dalam Mewujudkan Keadilan Kerja pada Organisasi di Indonesia - Mia Fazira; Dwi Ariza Zamzama Wulandari; Rofiqoturrohmah Rofiqoturrohmah; Rafika Meilia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the implementation of Equal Employment Opportunity and Affirmative Action in realizing workplace justice in organizations in Indonesia. Although both concepts are normatively designed to ensure equal opportunity and correct structural inequalities, their implementation still faces various obstacles, such as inconsistencies between formal policies and practices and low-effective oversight. This study uses a qualitative approach with a multi-method design through document study and limited empirical analysis, using conceptual, thematic, and regulatory analysis techniques. The results indicate that both concepts have a complementary relationship in creating workplace justice, but also have the potential to create conflict, particularly regarding the principle of meritocracy and employee perceptions of fairness. Furthermore, weak policy integration and a non-inclusive organizational culture are key inhibiting factors. This study contributes by strengthening the integrative conceptual framework and providing practical recommendations for organizations in designing more equitable and inclusive employment policies.